O(N/sup 2/ log N) native fan-beam tomographic reconstruction - Shu Xiao; Bresler, Y.; Munson, D.C. (2002 IEEE International Symposium on Biomedical Imaging : proceedings : July 7-10, 2002, Ritz-Carlton Hotel, Washington, D.C., USA, 2002)
We present a new fast backprojection algorithm for CT fan-beam reconstruction. The new algorithm operates directly on fan-beam data without prior rebinning to parallel-beam projections. The algorithm reduces the computational complexity from O(N/sup 3/) for the traditional fan-beam algorithm to O(N/sup 2/ log N). Simulations demonstrate speedups of greater than 50-fold for a 512 /spl times/ 512 image, with no perceivable degradation in accuracy. The algorithm also applies to multi-slice helical 3D reconstruction, and extends to 3D cone-beam reconstruction.